Improving the Vietnamese tea value chain in the international market the case of Thai Nguyen Province - Le Van Hung; Vu Ngoc Quyen; Nguyen Dinh Hoa (2019)
Tea production is considered the key sector in Thai Nguyen Province for its provision of livelihood to 40% of rural households. The province is also best known for its traditional green teas with a century history. Based on the primary data collected through field surveys and key informant interviews in Thai Nguyen city and Dai Tu district, the analysis of Thai Nguyen’s tea value chain was done by segments and key players. Thai Nguyen’s tea is mainly consumed domestically while tea in Vietnam in general is intended more for export. Results of the analysis showed significant differences in gaining profits among key players. In particular, tea growers with certified production earned more than those with non-certified farming practices. Better profits were also concentrated in the group of Kinh farmers and tea growers in Thai Nguyen City or in tea growing households with higher education levels and with production and/or market linkages. Lower profits from exports of tea materials and the decrease in export volumes in recent years would imply weak competitiveness of Thai Nguyen’s tea exports, which was mainly attributed to nonstandardized farming practices, small-scale production and non-rigorous control of food hygiene and safety. In order to improve the tea value chain in the international market, it is necessary to develop a quality-focused strategy for tea products in Thai-Nguyen province, improve the social recognition of GAP-certified households producing tea and provide incentives for GAP-adoption and renewal of certification, increase investment in irrigation infrastructure, provide adequate R&D funding for the diversification of tea products and development of environment-friendly packaging materials, plan and establish a processing cluster for tea products, and coordinate and support enterprises to provide updated market information and trade promotion for tea products.
Keywords: Tea; Production; Small-scale producers; Export marketing; International trade